Lysophosphatidylcholine: A Novel Modulator of Trypanosoma cruzi Transmission - Mário A. C. Silva-Neto; Alan B. Carneiro; Livia Silva-Cardoso; Georgia C. Atella (Journal of Parasitology Research)
Lysophosphatidylcholine is a bioactive lipid that regulates a large number of cellular processes and is especially present during the deposition and infiltration of inflammatory cells and deposition of atheromatous plaque. Such molecule is also present in saliva and feces of the hematophagous organism Rhodnius prolixus, a triatominae bug vector of Chagas disease. We have recently demonstrated that LPC is a modulator of Trypanosoma cruzi transmission. It acts as a powerful chemoattractant for inflammatory cells at the site of the insect bite, which will provide a concentrated population of cells available for parasite infection. Also, LPC increases macrophage intracellular calcium concentrations that ultimately enhance parasite invasion. Finally, LPC inhibits NO production by macrophages stimulated by live T. cruzi, and thus interferes with the immune system of the vertebrate host. In the present paper, we discuss the main signaling mechanisms that are likely used by such molecule and their eventual use as targets to block parasite transmission and the pathogenesis of Chagas disease.